Comparative calibration of corrosion measurements using K-nearest neighbour based techniques - Hamed, Y. (EDP Sciences, 2016)
Every measuring equipment or inspection tool is known to have its own accuracy, which may affect the reliability of its measurements. This includes oil and gas pipeline corrosion defects measurements. The inspection tolerance occurred in the measurements should be treated carefully for each equipment to prevent misinterpretation of the data which could lead to incorrect assessment. This paper presents a comparison between two K-Nearest Neighbour (KNN) interpolation techniques used to calibrate corrosion measurements collected by Magnetic Flux Leakage Intelligent Pig (MFL-IP) with the readings of Ultrasonic Testing (UT) scan device. The comparison has relied on the position of the interpolators, the weight sequence, and the error in the final enhanced metrics compared to the original measurements. Both techniques have the potential to calibrate and enhance IP measurements, with relative advantage for one technique in reducing over fitting problem. This enhancement will be used to improve the integrity assessment report that depends on the disturbed corrosion metrics of oil and gas pipelines, to decide whether the pipeline is fit for service or needs certain maintenance. Â© Owned by the authors, published by EDP Sciences, 2016.